Bibliometric Analysis of Human Capital Research: Focus on Talent Management and Organizational Performance - Loso Judijanto; Maiza Fikri; Mislan Sihite (Sciences du Nord Economics and Business, 2024)
This bibliometric analysis explores the evolving landscape of talent management research and its impact on organizational performance, utilizing data from major academic databases. By constructing a network of co-authorship and analyzing the density of research topics, the study identifies key themes and trends, as well as principal researchers and their collaborative patterns. The core areas of focus include talent development, employee engagement, and the strategic role of leadership in enhancing organizational outcomes. The study highlights the increasing emphasis on sustainable organizational performance and innovation, reflecting the growing integration of these concepts within talent management strategies. The findings offer valuable insights into the dynamic field of talent management, providing a robust foundation for future research and practical applications in both academic and corporate settings.